Nucleic acids and enzymes in Atlantic cod ( Gadus morhua ) differing in condition and growth rate trajectories - Dutil, Jean-Denis; Lambert, Yvan; Guderley, Helga; Blier, Pierre U; Pelletier, Dany; Desroches, Martine (Canadian Journal of Fisheries and Aquatic Sciences, 1998)
Atlantic cod (Gadus morhua) were exposed to one of four feeding regimes, 16 weeks of food deprivation (U) or satiation feeding (F) or two 8-week periods of food deprivation followed by satiation feeding (UF) or vice versa (FU), to determine whether relationships between nucleic acids or enzymes and growth rates result from a general enhancement of individual condition or are a direct result of enhanced growth rates. Final condition factor (K) differed between treatments, but did not differ between the mixed treatments after either 8 weeks of negative growth (FU) or 8 weeks of positive growth (UF). Intestinal cytochrome c oxidase activity matched the expected short-term growth rates, not only in fed and unfed fish but also in cod exposed to the mixed treatments (FU and UF). White muscle lactate dehydrogenase activity reflected growth rates, but initial levels were not reached within 8 weeks in FU cod. The liver glutamate pyruvate transaminase : DNA ratio reflected differences in K, but not differences in recent growth rates. Myofibrillar proteins decreased in unfed cod, while sarcoplasmic proteins followed changes in K more closely. The RNA:DNA ratio in white muscle did not reflect changes in K or changes in growth rates.